An Empirical Study on The Hydrogen Peroxide Reaction with Iodide in Acid Condition - Ayuni Dita Rosalia; Patiha Patiha; Eddy Heraldy (UNIVERSITAS SEBELAS MARET (UNS), 2015)
This research aimed to find out I- reaction order in the mechanism of hydrogen peroxide reaction with iodide in acid condition, to find out the form of rate law, and to show the role of H+ in reaction. The experiment for determining reaction order was carried out with isolation method using UV-Vis spectrophotometry. The order reaction was obtained from the r value approaching one, the results of its linear regression. The form of rate law was viewed from the presence or absence of oxygen gas. Meanwhile the role of H+ in reaction was determined by observing the pH value in 60 minutes.The result of experiment shows that the mechanism of reaction has rate law in the form of fraction, in which I- could be in zero and first orders. In addition, the rate law in this experimental condition is not an addition in the absence of O2 and relatively equal kobs value in the same order. The role of H+ is observed not as catalyst, but reactant.